Commentary: The Value of Patient Benefit: Consideration of Framing Contingencies to Guide the Ethical Use of DBS—a Case Analysis. (16th September 2016) - Giordano, James
Abstract : Here we have a case in which (1) the outcome(s) for the patient do not comport with the projected—or initially defined—outcomes of the research study, and (2) these outcomes represent cognitive and behavioral effects that are positively interpreted by the patient, but not by the patient's immediate family. The 6Cs approach, which frames the technique or technology—and its effects—within defined considerations of domains and dimensions, can be used as part of a multistep approach to addressing issues arising from the use of neurotechnology. 1 The approach recommends that the medical team consider the following domains and dimensions when engaging neuroethical analyses: The capacities and limitations of current neuroscience and technology (neuroS/T), and the capacity of the patient The consequences incurred by neuroS/T on recipients, families, and society in the short, intermediate, and long term The character of the recipient (e.g., patterns of cognition, emotion, and behavior) affected by neuroS/T The continuity of research and clinical care The contexts of need and value that influence the use or nonuse of neuroS/T Consent through provision of the most information possible 2